Simultaneous and enantiospecific quantification of primaquine and carboxyprimaquine in human plasma using liquid chromatography-tandem mass spectrometry - Hanpithakpong, W; Day, NPJ; White, NJ; Tarning, J (BioMed Central, 2022)
Background The enantiomers of the 8-aminoquinoline anti-malarial primaquine have different pharmacological properties. Development of an analytical method for simultaneous quantification of the enantiomers of primaquine and its metabolite, carboxyprimaquine, will support clinical pharmacometric assessments.